Participatory Transformation: SOAR Analysis of the Learning Process in Elementary Madrasahs - Sukmawati, Fitri; Mahsun, Moch.; Shohib, Moch.; Zahroh, Aminatuz; Syuhud, Syuhud (Universitas Islam Lamongan, 2025)
This study aims to investigate the effectiveness of the participatory transformation approach through the SOAR (Strengths, Opportunities, Aspirations, Results) framework in improving the quality of the learning process at Madrasah Ibtidaiyah Nurul Jannah Sawaran Lor Lumajang. A descriptive qualitative methodology was used, with data collected through active observation, in-depth interviews with madrasah principals, teachers, and students, and document analysis. The SOAR framework is specifically applied to map the madrasah's intrinsic strengths, development opportunities, collective aspirations, and expected outcomes. The research results show that the participatory SOAR analysis successfully mapped existing capabilities and challenges. Primary strengths include the quality of competent teachers and a supportive learning environment—key opportunities identified in digital technology integration and external support. Shared aspirations create an inclusive learning environment and develop graduates who are competitive and possess noble character. Evidence of the resulting transformation includes increased student motivation, engagement, and learning outcomes. The implementation of SOAR facilitates constructive dialogue and asset-centered strategic planning, making it an effective model for Islamic educational innovation.